UV-Assisted in Situ Synthesis of Silver Nanostructures in a Metallogel Network - Nguyen, Ngoc Thang; Liu, Jui Hsiang (Old Journal, 2018)
In this paper, we represent the green synthesis of silver nanostructures using a metallogel of silver ions incorporated with Cholesteryl Pyridine Carbamate (CPC) gelator as a soft template and the UV-induced reduction of silver ions to silver nanoparticles (AgNPs). The metallogel and AgNPs were characterized by UV-Vis spectroscopy, scanning electron microscopy (SEM) coupled with an energy dispersive spectrometer (EDS), and transmission electron microscopy (TEM). The results from UV-Vis analysis confirmed a 1/2 ratio of silver ion to the CPC ligand in the complex, and the stability constant of the complex (Kc) was about 1.03 × 10¹⁵ M⁻², indicative of very stable coordination of the complex in ethanol. Morphological measurements revealed the highly fibrous network structure observed in both the neat CPC gel and the metallogel. Furthermore, the formation of “hairy stem-like” hollow fibers containing AgNPs were observed in the metallogel after UV irradiation, which is a rare observation in other metallogels.